2013
DOI: 10.3855/jidc.3157
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of parvovirus B19 IgG and IgM antibodies among pregnant women in Oyo State, Nigeria

Abstract: Introduction: Human parvovirus B19 causes a wide range of complications in pregnant women including abortion, severe fetal anemia, nonimmune hydrops fetalis, and even intrauterine fetal death. However, there is a dearth of information on the prevalence of the virus among pregnant women in southwestern Nigeria. Methodology: Blood samples were collected from 231 pregnant women and screened for antibodies to human parvovirus B19 IgM and IgG using an enzyme immunosorbent assay kits. Results: Of the 231 women, 31 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 20 publications
(16 reference statements)
7
19
1
Order By: Relevance
“…IgM was positive in 3.3% of our study population; it indicates that acute HPV B19 infection is prevalent in our population. It is compatible with a previous study that showed an active transmission of the virus in the community (2). A similar study showed that a significant percentage of child-bearing women were at risk of primary infection which could adversely affect their pregnancy (18).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…IgM was positive in 3.3% of our study population; it indicates that acute HPV B19 infection is prevalent in our population. It is compatible with a previous study that showed an active transmission of the virus in the community (2). A similar study showed that a significant percentage of child-bearing women were at risk of primary infection which could adversely affect their pregnancy (18).…”
Section: Discussionsupporting
confidence: 80%
“…B19 IgG seroprevalence was 61.4%, with one subject positive for IgM in Sudan (15). In another study, of the 231 women in Nigeria, 45 (20%) were positive for parvovirus B19 IgG, 10 (4%) were positive for parvovirus B19 IgM (2). Also, seroprevalence of HPV B19 in 404 Tunisian pregnant women was 76.2% (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations